Clove oil, benzocaine and sodium chloride concentrations during the transport simulation of Nile tilapia - Bizarro, Yvonaldo Wlademir Saldanha; Navarro, Fernanda Keley Silva Pereira; Navarro, Rodrigo Diana (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The objective of this study was to evaluate the effect of different concentrations of clove oil (eugenol), benzocaine and sodium chloride on the induction, return time and survival rate of Nile Tilapia (Oreochromis niloticus) during the transport simulation of 5 hours. The experimental design was completely randomized, with 9 treatments in three replicates: Treatment 1: control, Treatment 2: benzocaine 20 mg / L, Treatment 3: benzocaine 40 mg / L, Treatment 4: eugenol 3 ml / L, Treatment 5: eugenol, Treatment 6: eugenol 3 ml + 5 g salt, Treatment 7: eugenol 6 ml + 10 g salt, Treatment 8: 5 g / L salt, Treatment 9: 10 g / L salt. No significant difference was observed for immediate survival rate, survival rate between 24 and 48 hours. In relation to the induction times, those were lower and significant for benzocaine 40 mg / L, eugenol 6 ml / L and the association between eugenol and salt (6 ml / L + 10 g) in comparison with other treatments. The return times of the anesthetics benzocaine 40mg / L, eugenol 6 ml / L and conjugation between eugenol and salt (6ml / L + 10g) were lower in relation to the treatments with lower concentration. The survival rate demonstrated satisfactory results in all treatments. However, benzocaine at 40 mg / L concentration was considered the most effective anesthetic for tilapia because it presented shorter induction and recovery times.